2020
DOI: 10.1177/0095244320959805
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the creep behavior of PA6 film based on the fractional differential model

Abstract: A fractional Burgers model was proposed to investigate the creep behavior of Polyamide 6 (PA6) film. The creep tests at various conditions were conducted on dynamic mechanical analysis (DMA) tester, and the strain-time ( ∊- t) curves of deformation were analyzed by the derived model. The results indicated that the fractional Burgers model had a better performance than the classical integer-order model in simulating the deformation of PA6 film. Parameters analysis showed that the stress facilitated the transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In recent years, the constitutive equation of fractional order operator has been increasing attention and research [14]. Fractional order rheological model with global correlation, by defining the differential and integral item, can use fewer parameters accurately describe a viscoelastic material temperature or in a wider frequency range of complex mechanical behavior [15]. It overcomes the disadvantage of inconsistent model fitting with experimental data when using integer-order models to deal with complex physical processes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the constitutive equation of fractional order operator has been increasing attention and research [14]. Fractional order rheological model with global correlation, by defining the differential and integral item, can use fewer parameters accurately describe a viscoelastic material temperature or in a wider frequency range of complex mechanical behavior [15]. It overcomes the disadvantage of inconsistent model fitting with experimental data when using integer-order models to deal with complex physical processes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research has found that biaxial stretching technology can promote the crystallization orientation of PLA molecular chains and effectively improve their mechanical properties (Jariyasakoolroj et al, 2015;Kong et al, 2015;Ouchiar et al, 2016;Ren et al, 2020;Ding et al, 2021;Liu et al, 2021;Yoksan et al, 2021;Lin et al, 2022;Zhou et al, 2022). For example, Jariyasakoolroj et al (Jariyasakoolroj et al, 2015) characterized the microstructure of biaxially oriented PLA (BOPLA) film and found that the small γmicrocrystals with isotropic properties were formed inside the film when the stretching rate and the stretching ratio increased simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical viscoelastic material, the mechanical behavior of PLA is closely related to the time, and there are apparent rheological phenomena during biaxial stretching (Yang and Kan, 2013;Li et al, 2016;Liu et al, 2021;Zhang et al, 2021). Therefore, studying the rheological behavior during biaxial stretching is of great significance in understanding the deformation mechanism of PLA films.…”
Section: Introductionmentioning
confidence: 99%